Application of typical error of measurement for accuracy of measurement of body composition in athletes using the bia method - Kutac, P. (Medicina Sportiva, 2012)
To ensure the interpretation of the measured results during repeated measuring, it is necessary to know the accuracy of measurement of the used method and device. One of the possibilities of expressing this error is to use typical error of measurement. Objective: To determine the actual error of measurement of the monitored body composition parameters when applying the bioelectrical impedance method in soccer players using typical error of measurement. Methods: The research included a group of 50 men whose average age was 20.35 ± 1.25 years; they were soccer players in the U21 age category. The measurement of the monitored parameters was carried out using the Tanita 418 MA device; the accuracy of measurement was determined using typical error of measurement and interclass correlation. Results: The found mean values of the typical error of measurement were 0.11 kg in body weight, 0.39 kg and 0.44% in the representation of body fat, and 0.26 kg and 0.35% in total body water. The interclass correlation values ranged from 0.983 to 1.000. Conclusion: The typical error of measurement allows us to determine actual errors of measurement expressed in the used measurement units. The measurement of body composition with the used device is sufficiently accurate for the needs of the practice of physical education.